Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Dalam Membayar Pajak Bumi Dan Bangunan - Yuwita Ariessa Pravasanti (ITB AAS INDONESIA, 2020)
This study aims to examine analysis of factors affecting on taxpayer compliance. This type of research includes quantitative research using primary data obtained directly by respondents using a questionnaire. The population in this study were all land and building taxpayers in Tawengan Village. The method used in the selection of samples is purposive sampling method using solvin formula and set samples based on criteria determined by researchers. Respondents in this study were 138 respondents. Based on the results of processing primary data (questionnaires) with multiple linear regression analysis methods, F test and t test known variables of taxation socialization, understanding taxation procedures, awareness of taxpayers and tax sanctions simultaneously significantly influence taxpayer compliance. Partially, this study shows that tax socialization and tax sanctions have a significant positive effect on tax compliance. While understanding taxation procedures and awareness of taxpayers does not have a significant influence on taxpayer compliance in paying land and building taxes